Distribution of absorbed dose by the perimeter and the length of the polymeric protective sheath at radiacinous irradiation of the ship cable - Bezprozvannych, G.V.; Mirchuk, I.A. (Вопросы атомной науки и техники, 2019)
The research of the distribution of the absorbed dose along the perimeter and length of the polymer protective sheath on the basis of a halogen-free composition depending on the technological dose of radiation exposure of shipboard cable samples was performed. It has been established that irregularity of irradiation around the cable perimeter can reach 20…30% with a technological dose in the range of 1.25…0.5. The irradiation along the cable is more uniform and does not exceed 5% at a technological dose in the range of 1.25…0.567. With a reduction in the technological dose, the irregularity of radiation around the perimeter and length of the cable increases. It is established that with an average absorbed dose of 210 kGy, the protective polymer shell does not meet the requirements of the standard for relative elongation at break. Optimal and physical-mechanical characteristics of the polymer shell made of halogen-free material are provided under irradiation in the range of the absorbed dose of 160 to 170 kGy. Проведено дослідження розподілу поглиненої дози по периметру і довжині полімерної захисної оболонки на основі безгалогенного матеріалу в залежності від технологічної дози опромінення зразків суднових кабелів. Встановлено, що нерівномірність опромінення по периметру кабелю може досягати 20…30% при технологічній дозі в діапазоні 1,25…0,5. Опромінення вздовж кабелю є більш рівномірним і не перевищує 5% при технологічній дозі в інтервалі значень 1,25…0,567. При менших значеннях технологічної дози збільшується нерівномірність випромінювання по периметру і довжині кабелю. Встановлено, що при середній поглиненій дозі 210 кГр захисна полімерна оболонка не відповідає вимогам щодо відносного подовження при розриві. Оптимальні фізико-механічні характеристики полімерної оболонки з безгалогенного матеріалу забезпечуються при опроміненні в діапазоні поглиненої дози 160…170 кГр. Выполнено исследование распределения поглощенной дозы по периметру и длине полимерной защитной оболочки на основе безгалогенной композиции в зависимости от технологической дозы радиационного облучения образцов судового кабеля. Установлено, что неравномерность облучения по периметру кабеля может достигать 20…30% при технологической дозе в диапазоне 1,25…0,5. Облучение кабеля по длине более равномерное и не превышает 5% при технологической дозе в интервале значений 1,25…0,567. При меньших значениях технологической дозы неравномерность облучения по периметру и длине кабеля увеличивается. Установлено, что при средней поглощенной дозе 210 кГр защитная полимерная оболочка не соответствует требованиям по относительному удлинению при разрыве. Оптимальные физико-механические характеристики полимерной оболочки из безгалогенного материала обеспечиваются при облучении в диапазоне поглощенной дозы 160…170 кГр.